IMPLEMENTASI SISTEM INFORMASI APLIKASI SIMPEL-SAKTI DALAM PENGAJUAN SURAT KETERANGAN DI BADAN KESATUAN BANGSA DAN POLITIK KOTA BANDUNG. - Nurul Azizah, Khoirun; Yusuf, Ramayani; Subrayanti , Delia; Azizah , Nur (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2024)
This study aims to describe the implementation of the SIMPEL-SAKTI application in submitting certificates at BAKESBANGPOL in Bandung City. This application facilitates the public in accessing online certificate services without having to come directly to the office. The research method used a descriptive qualitative approach through observation, interviews, and documentation. The results of the study show that SIMPEL-SAKTI reflects information system activities in the form of input, process, output, and feedback in the letter application procedure. The obstacles that arise include technical constraints such as unstable networks and limited features, as well as non-technical constraints in the form of low user understanding and a lack of service socialization.